2006
DOI: 10.1111/j.1708-8208.2006.00009.x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Clinical Study on Titanium Implants in the Zygomatic Arch for Prosthetic Rehabilitation of the Atrophic Edentulous Maxilla with a Follow‐Up of 6 Months to 5 Years

Abstract: The results from the present study show that the use of zygomatic and regular implants represents a predictable alternative to bone grafting in the rehabilitation of the atrophic edentulous maxilla.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
108
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(117 citation statements)
references
References 18 publications
4
108
0
3
Order By: Relevance
“…One randomized clinical trial, 16 16 prospective studies, [6][7][8]10,11,[17][18][19][20][21][22][23][24][25][26][27] and 51 retrospective analyses 1,2,9,13,28-74 were included. The only randomized clinical trial 16 was randomized for the performance of inferior meatal antrostomy.…”
Section: Description Of the Studies And Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…One randomized clinical trial, 16 16 prospective studies, [6][7][8]10,11,[17][18][19][20][21][22][23][24][25][26][27] and 51 retrospective analyses 1,2,9,13,28-74 were included. The only randomized clinical trial 16 was randomized for the performance of inferior meatal antrostomy.…”
Section: Description Of the Studies And Analysismentioning
confidence: 99%
“…2 Maxillectomy defects, maxillary sinus aplasia, and cleft deformities are even more challenging conditions. 3,4 The installation of zygomatic implants (ZIs) is one of the various techniques described in the literature to treat the atrophic maxilla, 5 and several prospective studies [6][7][8][9][10][11] have showed successful outcomes. A previous review on the survival of ZIs 12 observed that most failures were detected until 6 months after surgery, with a high 12-year cumulative survival rate (CSR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of this treatment modality was first developed to obtain anchorage and consequent stability in the zygomatic bone by the use of longer implants ([30 mm) and the placement of 2-4 standard implants in the anterior area to increase prosthesis support. In the past decades, this alternative to bone-grafting procedures has shown its predictability by demonstrating high survival rate ([95 % over a medium-/long-term follow-up) and few technical and biologic complications to bone grafting approaches in posterior maxilla and thus, its application in the routine rehabilitation for patients with severe atrophic maxilla [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Some examples of late complication are: loss of fixation or osseointegration, bucco sinusal communication, fenestration of the buccal mucosa, chronic sinusitis and sinus pathologies, palatal emergency of fixations, mucositis and peri-implantitis. (6)(7)(8)(9)(10)(11)(12)(13)(14) Recent systematic review studies reported the survival and presence of complications related of zygomatic fixation. (15) They conclude that the studies with a high level of evidence are scarce.…”
mentioning
confidence: 99%